A causal link between respiration and senescence in Podospora anserina - Dufour, Eric (The National Academy of Sciences, 2000)
Senescence, a progressive degenerative process leading to age-related increase in mortality, is found in most eukaryotes. However, the molecular events underlying aging remain largely unknown. Understanding how longevity is regulated is a fundamental problem. Here we demonstrate that the respiratory function is a key factor that contributes to shortening lifespan of the filamentous fungus Podospora anserina. In this organism, senescence is systematically associated with mitochondrial DNA instabilities. We show that inactivation of the nuclear COX5 gene encoding subunit V of the cytochrome c oxidase complex leads to the exclusive use of the alternative respiratory pathway and to a decrease in production of reactive oxygen species. This inactivation results in a striking increase of longevity associated with stabilization of the mitochondrial chromosome. Moreover, accumulation of several senescence-specific mitochondrial DNA molecules is prevented in this nuclear mutant. These findings provide direct evidence of a causal link between mitochondrial metabolism and longevity in Podospora anserina.